2020
DOI: 10.1002/da.23015
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of optimal dose of early intervention to prevent posttraumatic stress disorder: A multiarm randomized trial of one and three sessions of modified prolonged exposure

Abstract: Background: Posttraumatic stress disorder (PTSD) is linked to a specific event, providing the opportunity to intervene in the immediate aftermath of trauma to prevent the development of this disorder. A previous trial demonstrated that trauma survivors who received three sessions of modified prolonged exposure therapy demonstrated decreased PTSD and depression prospectively compared to assessment only. The present study investigated the optimal dosing of this early intervention to test one versus three session… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 36 publications
(43 reference statements)
2
26
0
Order By: Relevance
“…The low rate of eligible patients to recruit also poses a major limitation. Comparing these figures with previous studies on early interventions after trauma shows that a low rate of eligibility and recruitment is unfortunately common stressing the need for the field overall of finding ways around it (Rothbaum et al, 2012;Iyadurai et al, 2018;Maples-Keller et al, 2020).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The low rate of eligible patients to recruit also poses a major limitation. Comparing these figures with previous studies on early interventions after trauma shows that a low rate of eligibility and recruitment is unfortunately common stressing the need for the field overall of finding ways around it (Rothbaum et al, 2012;Iyadurai et al, 2018;Maples-Keller et al, 2020).…”
Section: Discussionmentioning
confidence: 81%
“…Results showed that PE was especially effective in reducing symptoms of post-traumatic stress among the subsample of rape victims (n = 47, 28% of the original sample) with a medium effect size (d = 0.7) at 12 weeks. A more recent study did not replicate these promising findings when comparing the three session protocol against one session and assessment only (Maples-Keller et al, 2020). However, this study had a much lower proportion of rape victims, and there was no separate subgroup analysis for this particular trauma type.…”
Section: Introductionmentioning
confidence: 73%
“…One of the most interesting findings of our study is that the prevalence of moderate-to-severe symptoms of PTSD is almost double the prevalence of anxiety symptoms. As mentioned previously, this result is likely to be influenced by the multiple traumatic experiences of staff in NCH (in terms of chronic stressors but especially of acute events in the aftermath of the infections peak) and the time since trauma exposure (all very recent experiences), which play a crucial role in determining the type and intensity of psychological symptoms [ 103 ]. PTSD is characterized by a specific pattern of psychological symptoms that is different in its etiopathology and clinical course from other psychiatric conditions (The ICD-11 Working Group [ 104 ]), and this could also subtend the difference in the prevalence rate of anxiety versus PTSD.…”
Section: Discussionmentioning
confidence: 99%
“…A randomised trial by Rothbaum et al (2012) found that a condensed three-session prolonged exposure (PE) intervention significantly reduced trauma symptoms compared to assessment only when provided 12–24 h after exposure to individuals at a hospital emergency department. However, a more recent study could not replicate these results when comparing the three-session protocol to one session and assessment only ( Maples-Keller et al, 2020 ). These null finding may be attributed to limited power and low symptom severity at baseline.…”
Section: Introductionmentioning
confidence: 97%